Penatalaksanaan Fisioterapi Pada Kondisi Post Sectio Caesarea Di RSUD Dr. Moewardi Surakarta - Rizki, Yesi Maha, Wahyuni, SSTFT, M.Kes (2016)
Background: Sectio caesarea is one of the actions to save the mother and fetus to form labor performed using a surgical procedure or incision to remove the baby from the womb by splitting abdomen. Problems that arise after sectio caesarea is pain at the incision and decreased functional activity. Modality physiotherapy use breathing exercise, gymnastic sporturition, kegel exercise, and transfer ambulation. Purpose: detected physiotherapy management in reducing pain, and increasing functional activity use modality breathing exercise, gymnastic sporturition, kegel exercise, transfer ambulation. Result: after therapy for about three times the obtained result of increase pain in painful T0: 5,2 cm to T6: 3,9 cm, tenderness T0: 10 cm to T3: 9,0 cm, motion pain T0: 6,9 cm to T3: 5,1 cm. increase functional activity T0: criteria value F to T3: criteria2 value A. Conclusion: breathing exercise, gymnastic sporturition, kegel exercise and transfer ambulation can reduce pain and increase functional activity in condition post sectio caesarea